Crafting racism, civilization, and margins through plaster busts of Icelanders. - Loftsdóttir, Kristín (Social Identities, 2023)
In the mid-nineteenth century, Iceland's small population under Danish rule tried establishing itself as part of Europe's civilized and progressive population. The production of racist texts and images that emphasized Iceland's natural place with 'progressive' European nations reflect Iceland's relationship with colonialism and the anxieties of being categorized with colonized others. The paper focuses on plaster casts of Icelandic faces, which were a part of collections meant to showcase racial diversity in the late nineteenth century in France and Spain. The analysis of the making and commercialization of the busts reflects one of the multiple ways Iceland was engaged in a world of imperialism and colonialism, underlining Iceland's ambiguous status in mid-nineteenth century Europe as a marginal European country. This status shaped Icelandic identity during the 19th and twentieth century, characterized by a strong need to position themselves as civilized subjects.